2022
DOI: 10.1177/03000605221119664
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative reproductive results of infertile patients with intrauterine adhesions: A retrospective analysis

Abstract: Objective To explore the reproductive outcomes after hysteroscopic separation of intrauterine adhesions (IUA) in infertile patients due to IUA. Methods This retrospective study enrolled patients with fertility requirements and infertility due to IUA. Data were collected from the hospital medical records and by follow-up by telephone. The impact on pregnancy and pregnancy outcome of preoperative adhesion, menstrual conditions before and after surgery and postoperative re-adhesion was analysed. Results A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Dilation & curettage (DC) is a surgery generally considered to be relatively safe, but it is still associated with some long-term complications. The most well-known complication is intrauterine adhesions, also known as Asherman syndrome, which may lead to menstrual disorders and fertility problems ( 69 ). Previous studies have shown that the uterus of Sprague Dawley (SD) rats presents a series of abnormal changes when intrauterine adhesions occur, such as a decreased number of endometrial glands, increased deposition of collagen and fiber deposition, and disorganized morphology and structure of the myometrium ( 70 , 71 ).…”
Section: Approaches To Establish the Pas Modelmentioning
confidence: 99%
“…Dilation & curettage (DC) is a surgery generally considered to be relatively safe, but it is still associated with some long-term complications. The most well-known complication is intrauterine adhesions, also known as Asherman syndrome, which may lead to menstrual disorders and fertility problems ( 69 ). Previous studies have shown that the uterus of Sprague Dawley (SD) rats presents a series of abnormal changes when intrauterine adhesions occur, such as a decreased number of endometrial glands, increased deposition of collagen and fiber deposition, and disorganized morphology and structure of the myometrium ( 70 , 71 ).…”
Section: Approaches To Establish the Pas Modelmentioning
confidence: 99%
“…Аномалии полости матки, в том числе ВМС (как дефект паттерна «эндометрий -миометрий») нарушают субэндометриальную перистальтику и, как следствие, служат причиной имплантационных неудач [57]. Аномальная волновая активность эндометрия затрудняет или вовсе препятствует миграции сперматозоидов, а в случае оплодотворения нарушает транспорт зиготы [58].…”
Section: Introductionunclassified